Grain Boundary Guided Folding of Graphene for Twisted Bilayer Graphene - Feiru Feng; Kun Zhou; Kang Zhang; Liya Wang; Ruijie Wang; Jun Xia; Chun Tang (Nanomaterials)
Bilayer graphene exhibits intriguing physical and mechanical properties that are suitable for advanced electronic device applications. By introducing a new degree of freedom through interlayer twisting, exotic phenomena such as superconductivity can arise. However, in practical experiments, manual manipulation is often required to fabricate such a configuration and therefore, scaled production of magic angle bilayer graphene is challenging. In this work, we propose utilizing the grain boundaries and accompanying localized out-of-plane deformation in graphene to facilitate twisted bi-layer graphene formation. Based on molecular dynamics simulations, the structure folding process along the boundary line is examined where a lower energetic cost is found. Once stabilized, the folded bilayer structure shows twist angles that differ visibly from the conventional AA or AB stacking modes and can achieve twist angles close to the 1.1° magic angle. This observation suggests a potential novel strategy for synthesizing stable twisted bilayer graphene or other two dimensional van der Waals heterostructures with greater efficiency.